SISTEM PENDIDIKAN DI NEGARA SINGAPURA - Abdul Wahab Syakrani; Abd. Malik; Hasbullah Hasbullah; Muhammad Budi; Muhammad Rifqi Maulidan (CV. ADIBA AISHA AMIRA, 2022)
Indonesia is still lagging behind Singapore in the field of education. It is evident from the difference in education levels between Indonesia and Singapore, namely, the difference is quite far in the level of basic education in Singapore, which is only 6 years while Indonesia takes 9 years with details of 6 years of elementary school and 3 years of junior high school, the next difference is in the country's secondary education level. Singapore takes 4 to 5 years at this level, while Indonesia takes 3 years but Singapore at this level classifies students' abilities into Express, Normal Academic and Normal Technical, while Indonesia only uses accelerated programs in certain schools. So completion at the intermediate level in Singapore takes 11 years, while in Indonesia it takes 1 year longer, which is 12 years.